La haine du renouvellement théorique : enquête sur la querelle théorique de la critique cinéphile et de l’Université française - Mathias Kusnierz (Mise au Point)
This paper examines the ideological and theoretical roots of a long-term quarrel between the intellectual criticism and the French University. The inquiry starts with recent statements and papers from French critics, such as the issue 698 of the Cahiers du cinéma. This paper aims to understand why the French critics disallow so violently every other approaches of the cinema than the aesthetics and speak in favor of a pluralistic idea of the research in cinema.